Disrupted host-microbiota crosstalk promotes nonalcoholic fatty liver disease progression by impaired mitophagy - Wenjing Yin; Wenxing Gao; Yuwei Yang; Weili Lin; Wanning Chen; Xinyue Zhu; Ruixin Zhu; Lixin Zhu; Na Jiao (Microbiology Spectrum)
ABSTRACT The intricate interplay between host genes and intrahepatic microbes is vital in shaping the hepatic microenvironment. This study aims to elucidate how host-microbiota interactions contribute to the progression of nonalcoholic fatty liver disease (NAFLD). Hepatic gene and microbial profiles were analyzed from 570 samples across five cohorts, including 72 control, 124 nonalcoholic fatty liver (NAFL), 143 Borderline, and 231 nonalcoholic steatohepatitis (NASH) samples. Least absolute shrinkage and selection operator penalized regression and sparse canonical correlation analysis were utilized to identify host-microbiota interactions and their function. Validation was performed using a bulk transcriptomic data set comprising 1,332 samples and a single-cell transcriptomic data set of seven samples. We observed stage-specific gene expression changes of disrupting energy metabolism and immune responses, alongside microbial shifts shaping the NAFLD microenvironment. Additionally, we identified 5,537, 1,937, 1,485, and 2,933 host-microbiota interactions in control, NAFL, Borderline, and NASH samples, respectively. Escherichia coli and Actinomyces naeslundii dominated the interaction network in control but were replaced by Sphingomonadales and Sphingomonadaceae in disease stages from NAFL, preceding the transcriptomic tipping point observed in Borderline. In NASH, interactions significantly weakened, accompanied by the loss of mutualistic interactions between bacteria such as Bacillales, Ralstonia insidiosa, Sphingomonadaceae, and host mitophagy genes including SQSTM1, OPTN, and BNIP3L. Single-cell data sets confirmed these interactions were co-localized in macrophages and monocytes in control, which shifted to hepatocytes and endothelial cells in NAFLD. Shifts in host-microbial interaction signal early microenvironment changes. Disturbed host-microbiota interactions impacting mitophagy can trigger a pro-inflammatory hepatic microenvironment, potentially driving disease progression.IMPORTANCEThis study integrated multiple cohorts to uncover fundamental and generalizable signals in the progression of nonalcoholic fatty liver disease. Key changes in both liver gene expression and microbiota were identified across disease stages, with microbial composition and interactions with host offering earlier insights into microenvironmental changes. Notably, host-microbiota interactions related to mitophagy, crucial in early stages, were destroyed in nonalcoholic steatohepatitis. This disruption may contribute to the worsening inflammation and disease progression.